Colorectal cancer treated by resection and extended lymphadenectomy: patterns of spread in left- and right-sided tumours. Issue 8 (4th April 2020) - Kataoka, K; Beppu, N; Shiozawa, M; Ikeda, M; Tomita, N; Kobayashi, H; Sugihara, K; Ceelen, W
Abstract: Background: Whether tumour side affects the anatomical extent and distribution of lymph node metastasis in colon cancer is unknown. The impact of tumour side on the anatomical pattern of lymphatic spread in colon cancer was assessed. Methods: Patients with stage III colon cancer from a Japanese multi-institutional database who underwent extensive (D3) lymphadenectomy, which is similar in concept to complete mesocolic excision with central venous ligation, were divided into groups with right- and left-sided tumours. Based on location, mesenteric lymph nodes were categorized as paracolic (L1), intermediate (L2) or central (L3). The Kaplan–Meier method was used to evaluate disease-free survival (DFS) and overall survival (OS), and multivariable Cox models were used to evaluate the association between anatomical lymph node level, metastatic pattern and outcome. Results: A total of 4034 patients with stage III colon cancer (right 1618, left 2416) were included. Unadjusted OS was worse in patients with right colon cancer (hazard ratio 1·23, 95 per cent c.i. 1·08 to 1·40; P = 0·002), but DFS was similar. Right-sided tumours more frequently invaded L3 nodes than left-sided lesions (8·5 versus 3·7 per cent; P < 0·001). The proportion of patients with a skipped pattern of lymphatic spread was higher in right than in left colon cancer (13·7 versus 9·0 per cent; P < 0·001). In multivariable analysis, invasion of L3 nodes was associated with worse OS in left but not in right colon cancer. The presence of skipped metastasis was associated with worse DFS in left, but not right, colon cancer. Conclusion: There are significant differences in the pattern of lymph node invasion between right- and left-sided stage III colon cancer, and in their prognostic significance, suggesting that tumour side may dictate the operative approach. Graphical Abstract: After adjustment for age, sex, pT category, tumour size, pattern of lymph node metastasis and lymph node ratio, overall survival was nearly identical in right colon cancer with invaded L2 or L3 nodes. In left colon cancer, however, overall survival was worse in L3-positive compared with L2-positive colon cancer. Right versus left-sided lymphatic drainage in colon cancer